rTMS Induces Brain Functional and Structural Alternations in Schizophrenia Patient With Auditory Verbal Hallucination - Xie, Yuanjun; Guan, Muzhen; Wang, Zhongheng; Ma, Zhujing; Wang, Huaning; Fang, Peng; Yin, Hong (Frontiers in Neuroscience, 2021)
Background: It has been suggested that low-frequency transcranial magnetic stimulation (rTMS) over the left temporoparietal cortex may reduce the auditory verbal hallucination in schizophrenia (AVH). However, the underlying neural basis of this rTMS effect remains not well understood. This study aims to investigate the rTMS induced brain functional and structural alternations and their associations with clinical and neurocognitive profiles in schizophrenia patients with AVH. Methods: Thirty schizophrenia patients with AVH and thirty-three matched healthy controls were enrolled. The patients were administered by 15 days of 1 Hz rTMS delivering to the left temporoparietal junction. Clinical symptoms and neurocognitive measurements were assessed pre- and post-rTMS. The functional (amplitude of low-frequency fluctuation, ALFF) and structural (gray matter volume, GMV) alternations were measured, and the altered functional and structural metrics was then predicted to the clinical and neurocognitive profiles post-rTMS in the patient group. Results: The results showed that the positive symptoms, including AVH, were relieved, and certain neurocognitive test scores, including visual verbal learning and verbal learning, were improved after the rTMS treatment in patients. Furthermore, the rTMS treatment caused brain functional and structural alternations, such as the increased amplitude of low-frequency fluctuation (ALFF) in the left superior frontal gyrus and enhanced gray matter volume (GMV) in the right inferior temporal cortex. These functional and structural alternations could further predict the improvement of positive symptoms and certain neurocognitive performance at post- treatment. Conclusion: The results suggested that the low-frequency rTMS is an efficacious treatment that selectively modulated the neural basis underlying symptoms and cognition in schizophrenia.